Exenatide and glucagon co-infusion increases myocardial glucose uptake and improves markers of diastolic dysfunction in adults with type 2 diabetes - Goodman, James; Schain, Martin; Di Stefano, Giovanni; Lupson, Victoria; Horn, Tracy; Hill, Marion; Manavaki, Roie; Fryer, Timothy D.; Bumanlag-Amis, Elaine; Jalaludeen, Navazh; Jermutus, Lutz; Johansson, Edvin; et al. (Scientific reports, 2025)
Type 2 diabetes (T2D) significantly increases the risk of heart failure, a major cause of hospitalisation and increased morbidity and mortality. Dual and multi-agonist synthetic peptides at the GLP-1 and glucagon receptor are in clinical development as potential new treatments for a range of chronic metabolic conditions including T2D. Here, we aimed to explore the effects of GLP-1 and glucagon dual receptor agonism on myocardial glucose uptake (MGU) and myocardial function in T2D. Eight adults with a mean age of 52 ± 12 years and body mass index 31 ± 4 kg/m 2 attended three randomised infusion visits using combinations of 0.9% saline, glucagon (12.5 ng/kg/min) and exenatide:glucagon co-infusion (exenatide loading dose 50 ng/min for 30 min then 25 ng/min). MGU and myocardial function were assessed using 18 F-FDG PET-MRI. MGU increased in n = 7/8 (88%) participants from a median of 9.2 × 10 −3 µmol/g/min (IQR 0.33–19 × 10 −3 µmol/g/min) with saline, to 20 × 10 −3 µmol/g/min (5.4–98 × 10 −3 µmol/g/min) with exenatide:glucagon, n = 8, z = 2.24, r = 0.79, P < 0.05. Exenatide:glucagon significantly increased the median left ventricular global peak diastolic circumferential strain rate from 0.619 1/s (0.580–0.716 1/s) to 0.686 1/s (0.644–0.737 1/s) n = 8, z = 2.37, r = 0.84, P < 0.05. Left ventricular global longitudinal contraction (as a measure global longitudinal strain) numerically increased by 0.6%, from − 16.0% with saline (-14.0-[-16.7]%) to -16.6% with exenatide:glucagon (-14.1-[-17.6]%), n = 8, z =-1.54, r=- 0.54, P = 0.123. Further studies are required to explore whether GLP-1/glucagon dual receptor agonists have a role to play in reducing cardiovascular risk and attenuating heart failure related outcomes in patients with chronic metabolic conditions such as T2D.